First naphthosemiquinone complex of K+ with vitamin K3 analog: experiment and density functional theory - Kathawate, Laxmi; Gejji, Shridhar P.; Yeole, Sachin D.; Verma, Prakash L.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2015)
Synthesis and characterization of potassium complex of 2-hydroxy-3-methyl-1,4-naphthoquinone (phthiocol), the vitamin K3 analog, has been carried out using FT-IR, UV-Vis, H-1 and C-13 NMR, EPR, cyclic voltammetry and single crystal X-ray diffraction experiments combined with the density functional theory. It has been observed that naphthosemiquinone binds to two K+ ions extending the polymeric chain through bridging oxygens O(2) and O(3). The crystal network possesses hydrogen bonding interactions from coordinated water molecules showing water channels along the c-axis. C-13 NMR spectra revealed that the complexation of phthiocol with potassium ion engenders deshielding of C(2) signals, which appear at delta = similar to 14.6 ppm whereas those of C(3) exhibit up-field signals near delta similar to 6.9 ppm. These inferences are supported by the M06-2x based density functional theory. Electrochemical experiments further suggest that reduction of naphthosemiquinone results in only a cathodic peak from catechol. A triplet state arising from interactions between neighboring phthiocol anion lead to a half field signal at g = 4.1 in the polycrystalline X-band EPR spectra at 133 K. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: C-13 NMR; DFT; hydrogen bonding; Naphthosemiquinone; Phthiocol; Vitamin K3

Reactions of 2,3-dibromonaphthalene-1,4-dione and pyridyl amines: X-ray structures, DFT investigations, and selective detection of the Hg2+ and Ni2+ ions - Aggrwal, Gunjan; Salunke-Gawali, Sunita; Gejji, Shridhar P.; Nikalje, Milind; Chakravarty, Debamitra; Verma, Prakash L.; Gosavi-Mirkute, Prajkta; Harihar, Shital; Jadhav , Mahesh; Puranik, Vedavati G. (Engineered Science, 2021)
<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">In this work, the products formed by the reaction between 2,3-dibromonaphthalene-1,4-dione with (pyridine-2-yl)methanamine and (pyridine-4-yl)methanamine are discussed in detial. The products 2-amino-3-bromonaphthalene-1,4-dione (<span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">A<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">) and 2-aminonaphthalene-1,4-dione (<span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">B(1)<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">) obtained are characterized through 1H and 13C-NMR, FTIR, mass spectrometry, single-crystal X-ray diffraction experiments, which are in conjunction with wB97X based density functional theory. <span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">compound <span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">A<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);"> can effectively and selectively detect Hg2+ and Ni2+ ions, and proposes a potential mechanism of action<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">.